Histological Features and Biocompatibility of Bone and Soft Tissue Substitutes in the Atrophic Alveolar Ridge Reconstruction - Carlo Maiorana; Mario Beretta; Davide Rancitelli; Giovanni Battista Grossi; Marco Cicciù; Alan Scott Herford (Case Reports in Dentistry)
The reconstruction of the atrophic alveolar ridges for implant placement is today a common procedure in dentistry daily practice. The surgical reconstruction provides for the optimization of the supporting bone for the implants and a restoration of the amount of keratinized gingiva for esthetic and functional reasons. In the past, tissue regeneration has been performed with autogenous bone and free gingival or connective tissue grafts. Nowadays, bone substitutes and specific collagen matrix allow for a complete restoration of the atrophic ridge without invasive harvesting procedures. A maxillary reconstruction of an atrophic ridge by means of tissue substitutes and its histological features are then presented.